2013
DOI: 10.1515/ntrev-2012-0083
|View full text |Cite
|
Sign up to set email alerts
|

Bioorthogonal chemistries for nanomaterial conjugation and targeting

Abstract: Bioorthogonal chemistries are covalent reaction pairs that proceed in the presence of biological components with complete specificity. A suite of reactions has been described to date that provides scientists and engineers with diverse operational characteristics for different applications. Nanomaterials in particular have benefitted from these new capabilities, resulting in improved coupling efficiencies and multifunctionality. In this review, we will discuss the application of bioorthogonal chemistries to dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…We note that TCO and PEG-TCO loading conditions were optimized in previous work to provide maximal reactive loading without affecting antibody binding affinity. 52 Antibody concentrations were determined by absorption measurement using a NanoDrop 2000 spectrophotometer. TMR modification level was determined to be ~2 dyes/antibody by absorption measurement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that TCO and PEG-TCO loading conditions were optimized in previous work to provide maximal reactive loading without affecting antibody binding affinity. 52 Antibody concentrations were determined by absorption measurement using a NanoDrop 2000 spectrophotometer. TMR modification level was determined to be ~2 dyes/antibody by absorption measurement.…”
Section: Methodsmentioning
confidence: 99%
“…[48][49][50] Recently, we improved the robustness and overall power of our chemical amplification (ChemAmp) technique by increasing the density of reactive TCO moieties on the antibody, which tend to bury within the antibody during bioconjugation procedures. 51 To date, the simple yet powerful ChemAmp technique has been employed to detect protein targets on live and fixed human cells, bacteria, and microvesicles using magnetic nanoparticles and QDs, 52 but it has not been applied to secreted proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, the IEDDA reaction stands out from other bioorthogonal reactions due to its unmatchable kinetics (rate constant of up to 10 6 M −1 s −1 ) and its high specificity and biocompatibility [ 25 ]. Specifically, this reaction has been used to conjugate antibodies, which were later conjugated with tetrazine or TCO and then applied to cell imaging, nanoparticle functionalization, and targeted antibody therapy [ 27 , 28 ]. Attending to its characteristics and applications, we selected this reaction as the basis of system development to increase ELISA sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…However, GNPs in combination with bioorthogonal labelling have not been explored for this purpose. This is remarkable, since the inverse use of bioorthogonal chemistry-to synthesize protein/DNA-modified gold particles-has been reported [32,33]. In these studies, no change in GNP size was observed and hydrophobic, organometallic and hydrophilic moieties could be introduced onto the particles.…”
Section: Bioorthogonal Labelling For Clem Imagingmentioning
confidence: 99%